Using the GRADE system in diagnostic strategy: the case of antiphospholipid syndrome. (October 2014) - de Abreu, M Mendes; Levy, RA; Wahl, D
Diagnostic strategy studies commonly focus on the accuracy of tests in diagnosing, and grading this body of evidence is a challenge in itself because (1) standard tools for grading evidence were designed for questions about treatment rather than diagnostic testing; and (2) the clinical usefulness of a diagnostic strategy depends on multiple links in a chain of evidence connecting the performance of a test to changes in clinical outcomes. The application of the GRADE approach requires a shift in clinicians' thinking to clearly recognize that, whatever their accuracy, diagnostic tests are valuable only if they result in improved outcomes for patients.